2017
DOI: 10.22452/jdbe.vol17no1.2
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors of Medical Waste Management Implementation in Healthcare Facilities in Nigeria: A Case Study

Abstract: Medical waste management (MWM) in developing countries such as Nigeria continue to lag in the development and implementation of successful MWM programs. The concentration of research on management practices, waste generation and characterization, disposal practices implies very little attention has been given to understanding the factors that are critical to implementing successful MWM programs. The aim of this study is therefore to identify critical factors of MWM success in developing countries, and assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…This study stresses the need for increased participation at both the internal (HCF) and external (ministry) levels in creating awareness about the risk potential of medical wastes and existing guidelines to encourage acceptable practices and enactment of specific legislation dealing with MWM (Baaki et al, 2017). To improve current practices, nurses must be well-equipped with skills and practices in managing medical waste.…”
Section: First Theme: Hospital Waste Practicesmentioning
confidence: 93%
See 1 more Smart Citation
“…This study stresses the need for increased participation at both the internal (HCF) and external (ministry) levels in creating awareness about the risk potential of medical wastes and existing guidelines to encourage acceptable practices and enactment of specific legislation dealing with MWM (Baaki et al, 2017). To improve current practices, nurses must be well-equipped with skills and practices in managing medical waste.…”
Section: First Theme: Hospital Waste Practicesmentioning
confidence: 93%
“…Many countries are now developing guidelines or policies to manage hospital waste. The study found that training, sensitisation, and awareness are considered the most critical factors, followed by environmental legislation in compliance with international environmental rules/regulations; and specific and elaborate regulations concerning medical waste (Baaki et al, 2017). Unfortunately, a study conducted by Rajan et al (2018) shows that the current classification system of SMW in national guidelines was not appropriate for safe collection and disposal (disposal techniques adopted for Ayurveda biomedical wastes are esewage/drains, incineration, and landfill).…”
Section: First Theme: Hospital Waste Practicesmentioning
confidence: 99%
“…These various types of medical waste are separated using a method called segregation. Segregation separates different medical waste streams according to their classifications and is an essential part of the medical waste management process [9]. The essence is to separate infectious/hazardous waste from non-infectious/nonhazardous waste and prevent contamination [15].…”
Section: Pathological Wastementioning
confidence: 99%
“…A working environment with unsafe healthcare waste management practices may result in exposure to infectious wastes by Healthcare workers, patients, and clients that could, in turn, create infection due to blood-borne pathogens [8]. According to Baaki et al [9], planning a hospital waste management system is complex and challenging since healthcare waste is unique and heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation